1998
DOI: 10.1136/vr.143.15.412
|View full text |Cite
|
Sign up to set email alerts
|

Early manifestations of granulocytic ehrlichiosis in dogs inoculated experimentally with a Swedish Ehrlichia species isolate

Abstract: Seven beagles were inoculated experimentally with a Swedish canine Ehrlichia species isolate to study its pathogenicity. With respect to the 16S rRNA gene sequence, the isolate was identical to the human granulocytic ehrlichiosis (HGE) agent and closely related to both Ehrlichia equi and E phagocytophila. After an incubation period of four to 11 days, the most prominent clinical signs were high fever for two to five days and depression. All the dogs developed profound thrombocytopenia, moderate leukopenia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 25 publications
5
82
0
3
Order By: Relevance
“…Seven of the eight dogs had increased alkaline phosphatase values. These findings are very similar to those described for dogs in Minnesota, Wisconsin, and Sweden (11,17,18). None of the dogs had hypoproteinemia, hypoalbuminemia, hyperamylasemia, or regenerative left shift, as previously reported (11,18).…”
Section: Vol 43 2005 a Phagocytophilum Variants In Dog Infections 799supporting
confidence: 80%
See 3 more Smart Citations
“…Seven of the eight dogs had increased alkaline phosphatase values. These findings are very similar to those described for dogs in Minnesota, Wisconsin, and Sweden (11,17,18). None of the dogs had hypoproteinemia, hypoalbuminemia, hyperamylasemia, or regenerative left shift, as previously reported (11,18).…”
Section: Vol 43 2005 a Phagocytophilum Variants In Dog Infections 799supporting
confidence: 80%
“…These findings are very similar to those described for dogs in Minnesota, Wisconsin, and Sweden (11,17,18). None of the dogs had hypoproteinemia, hypoalbuminemia, hyperamylasemia, or regenerative left shift, as previously reported (11,18). All but two of the dogs recovered rapidly, within 24 to 48 h after the initiation of treatment with doxycycline or tetracycline.…”
Section: Vol 43 2005 a Phagocytophilum Variants In Dog Infections 799supporting
confidence: 80%
See 2 more Smart Citations
“…A. phagocytophilum is transmitted to humans or animals by I. scapularis ticks in the northeast and upper midwest and by I. pacificus ticks in the western states (29,34,38). In Europe, I. ricinus is considered the main vector, but other ticks have also been implicated (27), and A. phagocytophilum occurs primarily in sheep and cattle and less frequently in humans than in the United States (2,7,10,13,15,(30)(31)(32)39 (25,27,33). Generally, human isolates can infect laboratory mice, but Massung et al (24) reported that strains isolated from wild deer cannot infect laboratory mice.…”
Section: Discussionmentioning
confidence: 99%